Novel green bio-milling technique for the synthesis of BaTiO3 nanoparticle using Saccharomyces cerevisiae - Uddin, Imran; Jaiswal, Adhish; Poddar, Pankaj (International Journal of Innovative Biological Research, 2013)
The development of a novel green top-down approach called bio-milling for synthesizing the oxide nanomaterials is an issue of topical interest. While a number of chemical processes are energy intensive and involve toxic chemicals. Here we report, at room temperature, bio-milling of chemically synthesized barium titinate (BaTiO3) particles by challenging the fungus Saccharomyces cerevisiae against aqueous solution of BaTiO3 to synthesize the biogenic nanoparticles. The extracellular breaking of microscaled BaTiO3 particles by extracellular biomolecules/proteins secreted by the fungus under stressed condition results in the formation of particles in nanoregime. XRD spectra and TEM analysis showed that BaTiO3 particles reduce to their size during the interaction with the fungus Saccharomyces cerevisiae and maintaining their phase and crystallinity after bio-milling process.